Targeting CCR7-PI3Kγ overcomes resistance to tyrosine kinase inhibitors in ALK-rearranged lymphoma - Mastini, Cristina; Campisi, Marco; Patrucco, Enrico; Mura, Giulia; Ferreira, Antonio; Costa, Carlotta; Ambrogio, Chiara; Germena, Giulia; Martinengo, Cinzia; Peola, Silvia; Mota, Ines; Vissio, Elena; et al. (Science translational medicine, 2023)
Anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKIs) show potent efficacy in several ALK-driven tumors, but the development of resistance limits their long-term clinical impact. Although resistance mechanisms have been studied extensively in ALK-driven non-small cell lung cancer, they are poorly understood in ALK-driven anaplastic large cell lymphoma (ALCL). Here, we identify a survival pathway supported by the tumor microenvironment that activates phosphatidylinositol 3-kinase γ (PI3K-γ) signaling through the C-C motif chemokine receptor 7 (CCR7). We found increased PI3K signaling in patients and ALCL cell lines resistant to ALK TKIs. PI3Kγ expression was predictive of a lack of response to ALK TKI in patients with ALCL. Expression of CCR7, PI3Kγ, and PI3Kδ were up-regulated during ALK or STAT3 inhibition or degradation and a constitutively active PI3Kγ isoform cooperated with oncogenic ALK to accelerate lymphomagenesis in mice. In a three-dimensional microfluidic chip, endothelial cells that produce the CCR7 ligands CCL19/CCL21 protected ALCL cells from apoptosis induced by crizotinib. The PI3Kγ/δ inhibitor duvelisib potentiated crizotinib activity against ALCL lines and patient-derived xenografts. Furthermore, genetic deletion of CCR7 blocked the central nervous system dissemination and perivascular growth of ALCL in mice treated with crizotinib. Thus, blockade of PI3Kγ or CCR7 signaling together with ALK TKI treatment reduces primary resistance and the survival of persister lymphoma cells in ALCL.
Keywords: Tumor Microenvironment; Anaplastic Lymphoma Kinase; nádorové buněčné linie; nádorové mikroprostředí; Protein Kinase Inhibitors; Crizotinib; krizotinib; Protein-Tyrosine Kinases; Receptors, CCR7; tyrosinkinasové receptory; nádory plic; Mice; Phosphatidylinositol 3-Kinases; Cell Line, Tumor; fosfatidylinositol-3-kinasy; receptory CCR7; inhibitory tyrosinkinasy; nemalobuněčný karcinom plic; anaplastický velkobuněčný lymfom; zvířata; Humans; Lymphoma, Large-Cell, Anaplastic; endoteliální buňky; Carcinoma, Non-Small-Cell Lung; Receptor Protein-Tyrosine Kinases; Tyrosine Kinase Inhibitors; anaplastická lymfomová kináza; tyrosinkinasy; myši; inhibitory proteinkinas; Lung Neoplasms; lidé; Endothelial Cells; Animals